Cytometry profiling of ex vivo recall responses to Coxiella burnetii in previously naturally exposed individuals reveals long-term changes in both adaptive and innate immune cellular compartments - Raju Paul, Susan; Scholzen, Anja; Reeves, Patrick M.; Shepard, Robert; Hess, Joshua M.; Dzeng, Richard K.; Korek, Skylar; Garritsen, Anja; Poznansky, Mark C.; Sluder, Ann E. (Frontiers in Immunology, 2023)
Q fever, caused by the intracellular bacterium Coxiella burnetii, is considered an occupational and biodefense hazard and can result in debilitating long-term complications. While natural infection and vaccination induce humoral and cellular immune responses, the exact nature of cellular immune responses to C. burnetii is incompletely understood. The current study seeks to investigate more deeply the nature of long-term cellular recall responses in naturally exposed individuals by both cytokine release assessment (n=55) and cytometry profiling (n=36). Individuals exposed during the 2007-2010 Dutch Q fever outbreak were grouped in 2015, based on a C. burnetii-specific IFNγ release assay (IGRA), serological status, and self-reported clinical symptoms during initial infection, into asymptomatic IGRA-negative/seronegative controls, and three IGRA-positive groups (seronegative/asymptomatic; seropositive/asymptomatic and seropositive/symptomatic). Recall responses following in vitro re-stimulation with heat-inactivated C. burnetii in whole blood,were assessed in 2016/2017 by cytokine release assays and flow cytometry, and in blood mononuclear cells by mass cytometry. Cytokine release analysis showed significantly elevated IL-2 responses in all seropositive individuals and elevated IL-1β responses in those recovered from symptomatic infection. Comparative flow cytometry analysis revealed significantly increased IFNγ, TNFα and IL-2 recall responses by CD4 T cells and higher IL-6 production by monocytes from symptomatic, IGRA-positive/seropositive individuals compared to controls. Mass cytometry profiling and unsupervised clustering analysis confirmed recall responses in seropositive individuals by two activated CD4 T cell subsets, one characterized by a strong Th1 cytokine profile (IFNγ+IL 2+TNFα+), and identified C. burnetii-specific activation of CD8 T cells in all IGRA-positive groups. Remarkably, increased C. burnetii-specific responses in IGRA-positive individuals were also observed in three innate cell subpopulations: one characterized by an IFNγ+IL-2+TNFα+ Th1 cytokine profile and lack of canonical marker expression, and two IL-1β-, IL-6- and IL-8-producing CD14+ monocyte subsets that could be the drivers of elevated secretion of innate cytokines in pre-exposed individuals. These data highlight that there are long-term increased responses to C. burnetii in both adaptive and innate cellular compartments, the latter being indicative of trained immunity. These findings warrant future studies into the protective role of these innate responses and may inform future Q fever vaccine design.